Molecular imaging of reduced renal uptake of radiolabelled [DOTA0,Tyr3]octreotate by the combination of lysine and Gelofusine in rats - Rolleman, E. J.; Bernard, B. F.; Breeman, W. A. P.; Forrer, F.; de Blois, E.; Hoppin, J.; Gotthardt, M.; Boerman, O. C.; Krenning, E. P.; de Jong, M. (Nuklearmedizin - NuclearMedicine, 2008)
Aim: In peptide receptor radionuclide therapy (PRRT) using radiolabelled somatostatin analogues, kidney uptake of radiolabelled compound is the major dose-limiting factor. We studied the effects of Gelofusine (20 mg) and lysine (100 mg) and the combination of both after injection of therapeutic doses of radiolabelled [DOTA0,Tyr3]octreotate (60 MBq 111In or 555 MBq 177Lu labelled to 15 μg peptide) in male Lewis rats. Methods: Kidney uptake was measured by single photon emission computed tomography (SPECT) scans with a four-headed multi-pinhole camera (NanoSPECT) at 24 h, 5 and 7 days p. i. and was quantified by volume of interest analysis. For validation the activity concentration in the dissected kidneys was also determined ex vivo using a gamma counter and a dose calibrator. Results: Gelofusine and lysine both reduced kidney uptake of [177Lu-DOTA0,Tyr3]octreotate significantly by about 40% at all time points. The combination of Gelo - fusine and lysine resulted in a 62% inhibition of kidney uptake (p < 0.01 vs. lysine alone). A weak but significant dose-response relationship for Gelofusine, but not for lysine, was found. In a study with [111In-DOTA0,Tyr3]octreotate, conclusions drawn from NanoSPECT data were confirmed by biodistribution data. Conclusions: We conclude that rat kidney uptake of radiolabelled somatostatin analogues can be monitored for a longer period in the same animal using animal SPECT. Gelofusine and lysine had equal potential to reduce kidney uptake of therapeutic doses of [177Lu-DOTA0,Tyr3]octreotate. The combination of these compounds caused a significantly larger reduction than lysine or Gelofusine alone and may therefore offer new possibilities in PRRT. The NanoSPECT data were validated by standard biodistribution experiments.
Keywords: Molecular imaging; somatostatin analogues; kidney; Gelofusine; lysine; NanoSPECT